Effectiveness of Think Aloud Pair Problem Solving and Case Study based Active Learning Techniques for Engineering Classroom - More, Supriya S.; Kadam, Dipali M. (Journal of Engineering Education Transformations, 2025)
Engineering and Technology is a very dynamic sector and change is very rapid. The knowledge gained in traditional classrooms, through online lectures, through search engines, online video books, and Wikipedia is just helping to understand the theoretical concepts. These information sources cannot develop abilities to apply the theoretical concept to real-world problems. This can be developed through experiential learning in workshops, industrial visits, field visits, etc. The advanced courses are not having this scope due to limited lab capacities, high instrument costs, a variety of instruments, quick revisions in technology, less number of industries, IP securities, and many more reasons. The Automobile sector is a vibrant one and the Automobile Engineering department is always facing these issues. This study presents the teaching-learning experience of the course Automotive Control Engineering which faces the above issues. The study was conducted for T.Y.B.Tech Automobile Engineering students for the years 2018-19. The aim of the study was to increase the concept implementation ability of the students. The theoretical knowledge that was being received through books, lectures, and search engines were used to correlate the working of advanced technology. Think Aloud pair problem-solving technique (TAPPS) and case study presentation of the real-world system tools have been used for the course delivery. The course attainment level of the experimental group increased by 11%. The students have shown enhancement in competencies like problem-solving, application of theoretical concepts, critical thinking, lifelong learning, etc. Learning from peers and in groups also improved classroom engagement and the joy of learning.